The Impact of Social Media Brand Communication and Word-of-Mouth Over Brand Image and Brand Equity - Alice Cynthia Dewi; Tantri Yanuar Rahmat Syah; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2020)
The importance of brand equity has been realised in recent times and the vast growth of social media users has reached many companies to use of such spaces to reach out to their customers and boost their brand communications. A social media has evolved as one of marketing tool to engage with customers however the studies regarding benefit for health care facility brand are not much reported. The present study focuses on how social media communication as well as word of mouth affect people perception towards brand hence brand image and brand equity. We investigated 200 social media users by using a standardized survey at one of health care facilities. Here, the samples were collected using non-probability sampling method with a purposive sampling technique. The data analysis used the structural equation modelling technique to investigate the interplay of firm-created, user-generated social media communication and word of mouth. The empirical result indicated both social media communication and word of mouth have a significant impact on brand equity, while firm-created content and word of mouth have a positive effect on brand image. Furthermore, brand image was shown to have a positive influence on brand equity. The study provides useful implications for marketing practitioner to actively participate in utilisation of social media for marketing communication.